ORGANIZING STUDENTS’ INDEPENDENT LEARNING ACTIVITIES TO DEVELOP PROFESSIONAL COMPETENCIES - Khalimjonova Mavludahon O‘ktamjon kizi (TADQIQOTLAR, 2026)
Abstract: This article explores the theoretical and practical aspects of organizing students’ independent learning activities to enhance their professional competencies. In the context of contemporary education, fostering independent learning skills has become a critical factor in preparing students for complex professional environments. The study examines various pedagogical strategies, emphasizing the role of self-directed learning, reflective practices, and competency- based approaches. The research synthesizes findings from recent studies to establish a conceptual framework that links independent learning with the development of critical professional skills, including problem-solving, analytical thinking, and practical application. The results highlight the effectiveness of structured independent learning tasks, digital tools, and personalized learning pathways in promoting the holistic development of students’ professional competencies. The implications of this study are relevant for curriculum designers, educators, and policymakers aiming to integrate autonomous learning methodologies into professional education.